2015
DOI: 10.1177/1076029615576738
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Human Killer Cell Immunoglobulin-Like Receptor and Multidrug Resistance Gene Polymorphisms in Children With Immune Thrombocytopenia

Abstract: The frequency of MDR1 polymorphisms was not associated with susceptibility to the development and clinical progression of the disease. However, KIR2 gene polymorphisms were independently associated with childhood ITP in Egyptian patients with highest prevalence among (KIRDL2-/KIRDS2-) genotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
2
3
1
Order By: Relevance
“…Our results are consistent with those reported by El-Beblawy et al, [ 23 ] where frequency of different ABCB1 genotypes and alleles were not significantly different between patients and controls as well as between newly diagnosed and chronic patients with ITP.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results are consistent with those reported by El-Beblawy et al, [ 23 ] where frequency of different ABCB1 genotypes and alleles were not significantly different between patients and controls as well as between newly diagnosed and chronic patients with ITP.…”
Section: Discussionsupporting
confidence: 93%
“…The discrepancy between our results and those reported in other studies can be attributed to small sample size (31 in Akin et al [1] study and 48 in EL-Beblawy et al [23] study vs 90 patients in our study), different ethnicities (Turkish in Akin et al [1] study and Chinese in Xuan et al [27] study vs Egyptians in our study) and different age (Adults in Xuan et al [27] study vs children in our study).…”
Section: Itemcontrasting
confidence: 98%
See 2 more Smart Citations
“…In the only other study to date investigating KIRs and ITP, El-Beblawy et al 99 performed comprehensive KIR genotyping in Egyptian children with childhood ITP. This study demonstrated that the KIR2DL2-/KIR2DS2-genotype was overrepresented in children with ITP compared with controls.…”
Section: Kirs and Itpmentioning
confidence: 99%